MICROBURETA A MICROESCALA TOTAL PARA TITULOMETRÍA (Chilean Journal of Scientific Education, 2023)
Two “home-made” microburets built with low cost materials are presented including integrated magnetic stirrer and support to show their use in titrimetric analysis with visual indication. Normalization of HC1 0.01 mol/L with previous normalized NaOH titrant solution yields an average end point volume of 0.5600 mL with a standard deviation of 0.05800 (1.03% relative std. dev.). Results obtained with 25 and 10 mL burets are compaired with 1 and 2 mL “home-made” microburets.
Keywords: Tbtal-microscale, titration, relative standard deviation